Research hotspots and trends in diabetes and insulin resistance: a bibliometric analysis - Zhang, Shaobo; Yan, Huixin; Cao, Di; Sun, Weichen; Li, Jingnan; Xu, Jing; Song, Bailin; Wu, Xingquan (Frontiers in Nutrition, 2024)
Background: Many previous studies explored the relationship between diabetes and insulin resistance(IR); however, addressing the research gap where no bibliometric analysis had been conducted to summarize and analyze these publications, we will undertake a comprehensive bibliometric analysis to investigate the current status and emerging trends in publications examining the association between diabetes and IR.We retrieved publications related to the interaction between diabetes and IR from the Web of Science Core Collection (WoSCC). By utilizing software such as CiteSpace, VOSviewer, and Excel 2019, we analyzed and extracted relevant information from the literature to identify and delineate the research hotspots and directions in the study of diabetes and IR.